Data on the genome analysis of the wild edible mushroom, Russula griseocarnosa - Fei Yu; Junfeng Liang (Data in Brief, 2019)
In the present article, we report data on the whole genome sequence of a wild edible and medicinal ectomycorrhizal fungus Russula griseocarnosa. The R. griseocarnosa genome consists of 64.81 Mb with a GC-pair content of 49.41%. The genome assembly consists of 471 scaffolds and 16128 coding protein genes. The coding protein genes was annotated in different databases (GO, KEGG and CAZys), respectively. The whole genome sequence and functional annotation provide important information for ectomycorrhizal fungus, which can be used as a basis for cultivation and breeding of R. griseocarnosa. The Whole Genome project of Russula griseocarnosa has been deposited at DDBJ/ENA/GenBank under the accession RMVF00000000. The version described is RMVF01000000. To further interpretation of the data provided in this article, please refer to the research article ‘Whole genome sequencing and genome annotation of the wild edible mushroom, Russula griseocarnosa’ [1]. Keywords: Russula griseocarnosa, Ectomycorrhizal fungus, Whole genome, Genome annotation